Comparative thermal and structural characterization of sintered nano-silver and high-lead solder die attachments during power cycling - Dai, Jingru; Li, Jianfeng; Agyakwa, Pearl; Corfield, Martin; Johnson, Christopher Mark (Institute of Electrical and Electronics Engineers, 2018)
13.5 mm × 13.5 mm sintered nano-silver attachments for power devices onto AlN substrates were prepared at 250 ºC and a pressure of 10MPa for 5 minutes and compared with Pb5Sn solder joint die attachments under constant current power cycling with an initial temperature swing of 50-175 ºC. Both the effective thermal resistance and microstructural evolution of the samples were monitored using transient thermal impedance measurement and non-destructive X-ray computed tomography at regular power cycling intervals. The results showed a gradual increase in the effective thermal resistance of the Pb5Sn solder joints from 0.047 to 0.133 K/W from zero to 41k power cycles, followed by a rapid escalation to 0.5018 K/W at 52k cycles. This was accompanied with the formation and development of oblique cracks within the Pb5Sn die attachments until delamination occurred at the solder/device and solder/substrate interfaces. By contrast, the effective thermal resistance of the sintered Ag joints remained almost constant at 0.040 K/W up to 116k power cycles. This was explained in terms of thermally induced continuation of densification of the sintered structure and the formation and development of networked vertical cracks within the sintered Ag die attachments, some of which further extended into the Cu tracks of the AlN substrate.